Genetic variation of leaf pigment content in a southern beech - Arias Rios, Jorge Andrés (2022)
Leaf pigment concentration varied among populations, watersheds and between two consecutive years. The highest concentration of pigments was found in 2018, but both years showed the same trend among populations. Physiological, morphological and phenological attributes are potentially adaptive traits that determine functional responses to certain environmental conditions. They are crucial for understanding adaptations to environmental variation along a species natural range. Our goal was to evaluate the variation in pigment traits among Nothofagus alpina populations in a common garden trial to infer local adaptation. We also aimed to test variation in pigment traits between two consecutive years and to analyze the correlation between pigment and phenological traits (i.e., day of the year to bud burst and to beginning of senescence, growing degree days, growing season length). We analyzed 400 individuals (65 open-pollinated families) from eight natural populations coming from four lake watersheds comprising the species range in Argentina. Pigment traits were estimated using a spectrophotometer and analyzed with linear mixed models (LMMs). Significant differences among fixed factors (populations and watersheds) were found in chlorophyll a, chlorophyll b, total chlorophyll, carotenoids and anthocyanins concentrations. Two populations were always the most contrasting ones. These results and the influence of the family factor on the variance of the pigment traits are evidence of the genetic control as well as of the potential adaptive value of leaf pigment content in N. alpina, giving a base for adaptation to a long-lasting change in climate. The highest values for all pigments were found in 2018, but among populations they showed the same trend for both years. Significant correlations between the population means of pigment concentrations and phenological traits were found.